Income management of newly married couple: Case of the urban Malay community - Joremi, Leylawati; Satar, Nurulhuda Mohd; Zakaria, Roza Hazli (Malaysian Consumer and Family Economics Association, 2019)
The Department of Islamic Development Malaysia reported high divorce rates among Malays with a marriage duration of fewer than five years. It appears that financial hardship is the main cause. To address this problem, in-depth interviews on five newly married couples were conducted. The phenomenological method was used to expose the approach taken in managing household income. Findings showed that independent money management allocation system was the preferred practice. However, to meet religious claims, husbands also allocated housekeeping allowances to their wives. Besides, despite being married and having the responsibility of their own family, responsibility towards parents was not neglected. Economic instability is not a reason for these couples to ignore the needs of parents and other family members. Indeed, for Muslim couples, religion and cultures affected the management of household income. © 2019, Malaysian Consumer and Family Economics Association. All rights reserved.